Characteristics of patients with erectile dysfunction in a family physician-led erectile dysfunction clinic: Retrospective case series. Issue 1 (1st May 2017) - Chiang, Lap Kin; Kam, Cheuk-Wai; Yau, Kin-Chung Michael; Ng, Lorna
Abstract : Objective: To examine the characteristics of patients with erectile dysfunction in a family physician led erectile dysfunction clinic; To review association of chronic disease spectrum and erectile dysfunction; To review initial treatment pattern and outcome. Design: Retrospective case series review. Subjects: All consecutive patients seen in a regional hospital family physician led erectile dysfunction clinic from April 2014 to March 2015. Main outcome measures: The severity of erectile dysfunction, based on International Index of Erectile Function (IIEF-5). The associated chronic comorbidities of patients. Treatment patterns and patient outcomes. Results: One hundred and eighty three patients presented with erectile dysfunction (ED) with mean age 58.7 (range 23 to 82) years old were seen during the study period. One hundred and twenty seven patients (69.4%) had comorbidity of chronic diseases, including 50.8% had hypertension, 38.8% had diabetes mellitus and 33.9% had hyperlipidaemia. Their mean body mass index was 25.2 kg/m 2, the mean blood pressure was 137.3/79.5 mm Hg (1 mm Hg = 0.133 kPa). According to IIEF-5 score, 50.3%, 30.6% and 18.6% had severe, moderate and mild erectile dysfunction respectively. The average duration of ED before seeking medical help was 3.9 years. Phosphodiesterase 5 (PDE5) inhibitors were prescribed to 119 patients (65%), and 57.1% of them achieved good response. Twenty nine patients (15.8%) were referred to other specialty for further management, including 27.6% had contraindication for PDE5 inhibitor. Conclusion: High proportion of erectile dysfunction patients had comorbitiy of chronic diseases. 57.1% of those patients receiving PDE5 inhibitors showed good response.